An Investigation into WASH-related Aspects of Unhygienic Menstrual Practices among Female Students in Colleges of Education in Anambra State - Nwoye, Theresa Nwakaego (MANDAILING GLOBAL EDUKASIA, 2024)
This study delves into the Water, Sanitation, and Hygiene (WASH)-related facets of unhygienic menstrual practices among female students enrolled in colleges of education in Anambra State, Nigeria. The study scrutinizes the availability and condition of sanitation facilities, access to clean water, disposal methods for menstrual waste, as well as the prevailing knowledge, attitudes, and socio-cultural norms related to menstruation. The research employed a survey design methodology, utilizing self-structured questionnaires distributed via Google survey to collect data from a sample of 100 female students. The questionnaire's content was validated by professionals in the field. The reliability of the instrument was assessed using Cronbach's coefficient alpha. Various statistical techniques, including frequency counts, percentages, mean, standard deviation and Analysis of Variance (ANOVA) were employed for data analysis. The findings revealed significant gaps in menstrual hygiene management. A majority of the female students faced challenges due to inadequate sanitation facilities and a lack of access to clean water. Unhygienic practices, including the use of unsuitable materials, were prevalent, leading to health risks such as urinary tract infections and discomfort. Additionally, social stigma and cultural taboos persisted, contributing to secrecy and misinformation surrounding menstruation. These results underscore the urgent need for targeted interventions. This study thus serves as a foundational step in advocating for comprehensive menstrual hygiene management in educational institutions and beyond.